1973
DOI: 10.1017/s0014479700023681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time and Rate of Application on Uptake of Fertilizer by Wheat

Abstract: SUMMARYThe efficiency of fertilizer N uptake by wheat, as affected by time and rate of application, was studied in the field using N15 labelled ammonium nitrate. Splitting the application was only beneficial at the maximum rate but two top dressings at tillering and boot stage were better for grain production than a basal dressing or single top dressing at stem extension stage, but uptake of fertilizer N was maximal from a single top dressing. The calculated effective rate of application (E.R.A.) was useful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Our results are also comparable with [12-14] who reported that P applied as a split dose at planting stage or different growth stages by the method of side dressing, or 2nd application with irrigation, resulted more grain yield as compared to full application at sowing time. Similar findings were also reported by [15][16][17][18]. Dry matter yield Dry matter yield of wheat was significantly increased over control with acidulation levels of RP, forms of P fertilizers and application methods at P< 0.05 ( Table 2).…”
Section: Grain Yieldsupporting
confidence: 88%
“…Our results are also comparable with [12-14] who reported that P applied as a split dose at planting stage or different growth stages by the method of side dressing, or 2nd application with irrigation, resulted more grain yield as compared to full application at sowing time. Similar findings were also reported by [15][16][17][18]. Dry matter yield Dry matter yield of wheat was significantly increased over control with acidulation levels of RP, forms of P fertilizers and application methods at P< 0.05 ( Table 2).…”
Section: Grain Yieldsupporting
confidence: 88%
“…This agrees with frequent reports of an inverse correlation between grain yield and percent grain protein (Loeffler and Busch 1982;Nass et al 1976). Hamid (1973) found that splitting N application of 120 kg ha -1 between seeding and stem extension gave higher N in the grain than applying all of that amount at seeding; there was slightly more N in the straw and greater recovery of fertilizer N in the grain and straw. Sandhu and Gill (1971) found split application (2-3 times) gave the best protein response to N.…”
Section: Proteinmentioning
confidence: 94%